Activity-dependent gene expression in honey bee mushroom bodies in response to orientation flight - Lutz, Claudia C.; Robinson, Gene E. (Journal of experimental biology, 2013)
The natural history of adult worker honey bees (Apis mellifera) provides an opportunity to study the molecular basis of learning in an ecological context. Foragers must learn to navigate between the hive and floral locations that may be up to miles away. Young pre-foragers prepare for this task by performing orientation flights near the hive, during which they begin to learn navigational cues such as the appearance of the hive, the position of landmarks, and the movement of the sun. Despite well-described spatial learning and navigation behavior, there is currently limited information on the neural basis of insect spatial learning. We found that Egr, an insect homolog of Egr-1, is rapidly and transiently upregulated in the mushroom bodies in response to orientation. This result is the first example of an Egr-1 homolog acting as a learning-related immediate-early gene in an insect and also demonstrates that honey bee orientation uses a molecular mechanism that is known to be involved in many other forms of learning. This transcriptional response occurred both in naïve bees and in foragers induced to re-orient. Further experiments suggest that visual environmental novelty, rather than exercise or memorization of specific visual cues, acts as the stimulus for Egr upregulation. Our results implicate the mushroom bodies in spatial learning and emphasize the deep conservation of Egr-related pathways in experience-dependent plasticity.